2018
DOI: 10.3390/nu10020221
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Whey Protein Supplementation on the Temporal Recovery of Muscle Function Following Resistance Training: A Systematic Review and Meta-Analysis

Abstract: Whey protein (WP) is a widely consumed nutritional supplement, known to enhance strength and muscle mass during resistance training (RT) regimens. Muscle protein anabolism is acutely elevated following RT, which is further enhanced by WP. As a result, there is reason to suggest that WP supplementation may be an effective nutritional strategy for restoring the acute loss of contractile function that occurs following strenuous RT. This systematic review and meta-analysis provides a synthesis of the literature to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 39 publications
4
52
0
3
Order By: Relevance
“…The present meta-analysis is, to date, the largest in terms of RT interventions on full body muscle mass gain. Most meta-analyses that have analysed the effect of RT and characteristics of participants on muscle mass gains have only included works with protein supplementation [6,[122][123][124][125][126][127][128][129] or have analysed single variables of the training load isolated, as for example, training frequency [130][131][132], intensity or training periodization [133]. This segmentation has meant that many of the works that have focused solely on these analyses have been left out.…”
Section: Discussionmentioning
confidence: 99%
“…The present meta-analysis is, to date, the largest in terms of RT interventions on full body muscle mass gain. Most meta-analyses that have analysed the effect of RT and characteristics of participants on muscle mass gains have only included works with protein supplementation [6,[122][123][124][125][126][127][128][129] or have analysed single variables of the training load isolated, as for example, training frequency [130][131][132], intensity or training periodization [133]. This segmentation has meant that many of the works that have focused solely on these analyses have been left out.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the muscle metabolic response, from a practical standpoint we were also interested in examining the effect of supplemental whey protein on postexercise muscle recovery during the RT-protocol. Indeed, several studies have reported that protein supplementation facilitates temporal recovery after RT by improving neuromuscular function [15,16], exercise performance [13,15], reducing muscle damage [13] and muscle soreness [32], providing an obvious benefit to athletes who regularly engage in RT. Although alternative mechanisms have been proposed [32], it is commonly accepted that supplemental dietary protein enhances muscle recovery by accelerating the reconditioning, specifically of the myofibrillar (force-generating) protein fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplements creatine monohydrate (CR) and whey protein (WP) have previously demonstrated ergogenic roles in exercise performance and recovery, and subsequent adaptations from exercise training [ 8 , 9 ]. However, the effects of CR and WP supplementation on indicators of muscle damage and recovery after injury in both human [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] and animal [ 26 , 27 , 28 ] models are equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of WP supplementation studies have focused on the purported benefits of higher protein intake during periods following damaging exercise to enhance recovery [ 9 ]. White and colleagues [ 16 ] found no significant improvement in the rate of muscle recovery following maximal isokinetic eccentric contractions of the quadriceps when WP (23 g) was ingested pre- or post-exercise.…”
Section: Introductionmentioning
confidence: 99%